2014
DOI: 10.1590/s1806-66902014000400012
|View full text |Cite
|
Sign up to set email alerts
|

Controle do capim-braquiária associado à nutrição com boro no cultivo do mogno-africano em sistema silvipastoril

Abstract: Controle do capim-braquiária associado à nutrição com boro no cultivo do mogno-africano em sistema silvipastoril ). As subparcelas foram constituídas pela ausência ou presença de 4 kg de ácido bórico (17% B) para 100 L de água. A associação do ácido bórico aos herbicidas glyphosate mais chlorimuron-ethyl, glyphosate mais imazethapyr, glyphosate ou oxyfluorfen não interfere no controle do capim-braquiária. A adição do ácido bórico à calda dos herbicidas proporciona incrementos nos teores de boro no solo e, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
5
1
1
Order By: Relevance
“…ha -1 . Still regarding isoxaflutole, Brighenti & Muller (2014) found greater phytotoxic effects in doses lower than those used in this study in African mahogany (Khaya ivorensis) and Australian cedar (Toona ciliata var. australis) seedlings.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…ha -1 . Still regarding isoxaflutole, Brighenti & Muller (2014) found greater phytotoxic effects in doses lower than those used in this study in African mahogany (Khaya ivorensis) and Australian cedar (Toona ciliata var. australis) seedlings.…”
Section: Resultscontrasting
confidence: 62%
“…Similar to pre-emergence application of herbicides chlorimuron-ethyl and clomazone, their postemergence application led to mild initial symptoms of toxicity (≤8.5%), which dissipated during the experiment, followed by recovery of the treated plants. Brighenti & Muller (2014) did not see toxicity in African mahogany plants after application of chlorimuron-ethyl (7.5 and 12.5 g a.i. ha -1 ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The herbicides chlorimuron-ethyl, fomesafen, nicosulfuron, and bentazon caused visual injuries in plants at all evaluated times, except for chlorimuron-ethyl and fomesafen, which provided symptoms of intoxication that disappeared at the last evaluated period (42 DAA) ( Table 5). Brighenti and Muller (2014) observed no symptoms of intoxication in African mahogany with the application of chlorimuron-ethyl. Oliveira Júnior et al (2011) pointed out that selectivity to herbicidescan be obtained by means of physiological and morphological differences between 6 plant species, which may explain the different results found between Peruvian peppertree and African mahogany.…”
Section: Peruvian Peppertree (Schinus Molle) Jaboticabalmentioning
confidence: 78%
“…Also, there were no symptoms of injury caused by this herbicide in all the evaluated period. Brighenti and Muller (2014) reported that nicosulfuron application in African mahogany and Australian cedar at a dose of 40 g ha -1 presented slight and medium symptoms of intoxication at 14 and 21 DAA, respectively, with a lower dry matter accumulation in Australian cedar plants. In our study, nicosulfuron (50 g ha -1 ) provided visual toxicity from 7 to 42 DAA in Peruvian Means followed by the same letter in the column do not differ from each other by Student t test (p>0.05).…”
Section: Peruvian Peppertree (Schinus Molle) Jaboticabalmentioning
confidence: 99%